2020
DOI: 10.2147/jhc.s275008
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cross-Linked Multimeric Pro-Peptides of Type III Collagen (PC3X) in Hepatocellular Carcinoma – A Biomarker That Provides Additional Prognostic Value in AFP Positive Patients</p>

Abstract: Purpose: Non-invasive biomarkers for diagnosing and prognosing hepatocellular carcinoma (HCC) are urgently needed. Cirrhosis is present in 80-90% of HCC patients. Cirrhosis is characterized by deposition and cross-linking of collagens that have crucial roles in HCC initiation and progression. We evaluated circulating cross-linked pro-peptides of type III collagen (PC3X) as a diagnostic and prognostic biomarker for HCC. Patients and Methods: PC3X was measured by ELISA in plasma from patients with HCC (n=79), ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…During the past few years, biomarkers originating from the fibrotic TME have gained more attention [18]. We and others have shown that non-invasive biomarkers measuring ECM turnover products from fibroblast-derived collagens are increased in various cancer types and predictive of survival and treatment response [19][20][21][22][23][24][25]. As an example, PRO-C11-511, a biomarker measuring the pro-peptide of type XI collagen has shown to be increased in serum from patients with PDAC and is predictive of survival [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few years, biomarkers originating from the fibrotic TME have gained more attention [18]. We and others have shown that non-invasive biomarkers measuring ECM turnover products from fibroblast-derived collagens are increased in various cancer types and predictive of survival and treatment response [19][20][21][22][23][24][25]. As an example, PRO-C11-511, a biomarker measuring the pro-peptide of type XI collagen has shown to be increased in serum from patients with PDAC and is predictive of survival [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C4G, a biomarker measuring granzyme B degraded type IV collagen, assesses T-cell response and can identify patients with malignant melanoma responding to immune checkpoint inhibitors [19]. Fibrillar collagens are the most well-studied collagens, and the two fibrillar fibroblast-derived collagens, type IIIand VI collagen, have shown potential as biomarkers in cancer [19,20,22,23,25,26]. Type III and VI collagens are present in most tissue within the interstitial matrix of the ECM and are augmented in many cancer diseases [20,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The specific collagen turnover in the primary tumor and sites of secondary metastases is sufficiently high compared to in healthy tissue and benign and nonmalignant tissues of comparable organs (e.g. pancreatic cancer versus chronic pancreatitis, liver cancer versus cirrhosis, lung cancer versus idiopathic pulmonary fibrosis) [ 93 95 ]. Kehlet et al showed that formation of type III collagen (PRO-C3), and MMP-degradation of type I, III, and IV collagen (C1M, C3M, and C4M) were elevated in stage IV CRC patients compared to stage I, II, and III CRC patients and healthy controls [ 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…PRO-C3 has been shown to associate to a higher extent than PRO-C6 to liver fibrosis [ 45 , 46 ]. PRO-C3 has previously been investigated as a marker of degree of liver fibrosis as well as survival in cohort presented here [ 47 ]. Jensen C et al reported that PRO-C3 was related to the degree of liver fibrosis, however, it was not a predictor of survival in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen C et al reported that PRO-C3 was related to the degree of liver fibrosis, however, it was not a predictor of survival in patients with HCC. Nevertheless, a multimeric version of the assay, assessing the cross-linked species of PRO-C3, known as PC3X, was related to survival in HCC patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%